Treatment of enterocutaneous fistula with total parenteral nutrition in combination with octreotide: a case report - Antonia Alfirević; Dina Ljubas Kelečić; Patricia Barić; Ana Barišić (Liječnički vjesnik, 2023)
Octreotide is an analog of the polypeptide hormone somatostatin, which can reduce gastrointestinal, biliary and pancreas secretion, as well as decrease gastrointestinal motility. Octreotide in combination with total parenteral nutrition (TPN) has proven to be effective therapy in patients with high-output enterocutaneous fistula (EF).